The Influence of Environmental, Social and Governance Performance on Financial Performance with Company Type ad Moderator - Putri, Anjelia; Adrianto, Fajri; Rahim, Rida (DINASTI RESEARCH, 2025)
This study aims to determine the influence of Environmental, Social, and Givernance Performance on Financial Performance. This research method used is a quantitative method. The data used in this study is secondary data in the form the websited (www.idx.co.id) and Refinitiv Eikon. The population in this study are companies listed on the Indonesia Stock Exchange (IDX) for the period 2014 - 2023. The sample was selected from the purposive sampling method and obtained a sample of 35 companies from several predetermined criteria. The analysis technique used in this research is panel regression analysis with the help of Eviews version 12. The results of the analysis show that Environmental Performance has no significant positive effect on Financial Performance. Social Performance has a positive and significant effect on Financial Performance. Governance performance has a negative and significant effect on financial performance. Environmental Performance has no significant effect on Financial Performance moderated by Company Type. This research can contribute to add literature related to additional considerations such as Environmental Performance, Social Performance, Governance Performance and Financial Performance for investors in evaluating the company's potential.